2019
DOI: 10.1177/0961203319886028
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of predominant Lupus Low Disease Activity State (LLDAS-50)

Abstract: Aim The Lupus Low Disease Activity State (LLDAS) is a potential treat to target goal in systemic lupus erythematosus (SLE). SLE patients in LLDAS for more than half of the observation time have about a 50% lower risk of new organ damage and have reduced mortality. We identified predictors of being in LLDAS ≥50% of the observation time. Methods A total of 2228 SLE patients who had at least three clinical visits were included. Percentage of time in LLDAS was calculated based on the proportion of days under obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 48 publications
3
23
0
1
Order By: Relevance
“…These results dovetail with qualitative work in which people with SLE report pain and fatigue as among the most frequent or problematic aspects of the disease and describe their negative impact on social, leisure and family participation. 32,33 Interestingly, other common manifestations of SLE that have been found to affect activities of daily living and health-related quality of life, such as depressive symptoms, anxiety and sleep problems, 14 were not independently related to participation in our sample. These factors are known to be related to cognition, fatigue, and pain and to each other in SLE, 33 so it is possible that their contributions to participation were masked.…”
Section: Discussionmentioning
confidence: 63%
“…These results dovetail with qualitative work in which people with SLE report pain and fatigue as among the most frequent or problematic aspects of the disease and describe their negative impact on social, leisure and family participation. 32,33 Interestingly, other common manifestations of SLE that have been found to affect activities of daily living and health-related quality of life, such as depressive symptoms, anxiety and sleep problems, 14 were not independently related to participation in our sample. These factors are known to be related to cognition, fatigue, and pain and to each other in SLE, 33 so it is possible that their contributions to participation were masked.…”
Section: Discussionmentioning
confidence: 63%
“…The probability of patients achieving these states seems to vary according to a number of factors including race/ethnicity, in particular African ancestry, 8 9 age at diagnosis, 10 previous disease activity, 8 10 11 major organ involvement 10 12 and treatment. [8][9][10] Furthermore, the clinical impact of achieving such states in several clinical outcomes has been examined. 13 The outcome most frequently evaluated has been organ damage accrual; in fact, in several cohorts, remission and/or LDA have been found to prevent damage, but the exact definitions used for these states have not been uniform.…”
Section: Key Messagesmentioning
confidence: 99%
“…Several studies have shown that the risk of damage decreases with the length of time in either LLDAS or remission. While low disease activity intuitively appears to be a less desirable outcome than remission, patients in the LLDAS nevertheless achieve significantly better scores on both the SLE Quality of Life questionnaire and the 36-item Short Form Health Survey [ 76 ], reduced direct healthcare costs [ 77 ], damage and mortality than those with active disease [ 78 ]. Importantly, patients who spent even a short time in clinical remission (even <25% of visits) had a significant decrease in the rate of damage compared with never achieving remission.…”
Section: Long-term Outcomes In Sle: Trends Over Time and Major Contrimentioning
confidence: 99%